Profil Glukosa dan Urea Darah Sapi Bali Jantan yang digemukkan dengan Pakan Komplit yang Mengandung Level Protein Kasar berbeda - Silvester Egi Luan; Paulus Klau Tahuk; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study was to determine the glucose and urea profile of Bali bovine blood fattened with complete feed containing different levels of crude protein (PK). Cattle used by male Bali cattle are 2 - 2.5 years old with an initial weight of 200 kg. The rations used in the manufacture of complete feed are prepared with feed ingredients such as: natural grass, gliricida sepium, rice bran, corn flour, pollard bran. The variables measured in the study were blood glucose and blood urea of male Bali cattle. The method used is an experimental method using a completely randomized design (CRD) with the following treatment: T1: 27% Natural Grass + Gliricida sepium 10% + Corn Flour 34% + Pollard 15% + Rice Bran 14% T2: Natural Grass 27% + 20% Gliricida Sepium + 18% Corn Flour + 15% Pollard + 10% Rice Bran T3: 27% Natural Grass + 13% gliricida sepium + 20% Corn Flour + 15% Pollard + 7% Rice Bran The results of this study indicate that, the use of complete feed with different PK levels does not affect the glucose and urea levels of blood of Bali bulls (P> 0.05). Where the blood glucose level for each treatment is, T1: 92,392 ± 9,779, T2: 87,448 ± 7,905 T3: 93,717 ± 14,969 while the blood urea levels for each treatment are T1: 44,629 ± 5,663, T2: 45,473 ± 4,152, T3: 44,543 ± 8,343. Based on description of the results of the research that has been done, it can be concluded that the provision of complete feed with PK level (11%, 13%, 15%) at 72% TDN has the same effect for all treatments and produces blood glucose and urea levels in the normal range.